Application of Cooperative Learning Type Team Game Tournament (TGT) to Improve Studentsâ Mathematics Learning Outcome - Farida, Farida; Zetriuslita, Zetriuslita; Syofni, Syofni (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The aims of this researchis increase the mathâs study achivement by applyed time game tournament of Cooperative Learning Type in 2011, on the subject matter of relations and functions. This research uses a learning model of Team Game Tournament type. This research consists of the following stages: (1) initial reflection; (2) planning; (3) implementation of the action; (4) observation; (5) reflection. Researchers perform needs analysis, then prepare the material to be presented, as well as the necessary tools and tools in the form of syllabus, learning implementation plan , student worksheet , envelope cards, numbered cards and game scoring sheets. Furthermore, learning is presented as many as eight meetings in two cycles, with sabjek is 33 students. Average learning outcomes of students had an increase compared to the baseline score of 54.06 in the daily test I increased to 73.33, in the daily test II 66.36.